Inclusion of environmental criteria in public procurement in Costa Rica: Office supplies - Gamboa-Castro, Juan José (2018)
The public sector is the main consumer of the country; therefore, it has the capacity to drive markets towards sustainable production models. Costa Rica has initiatives to promote green and sustainable public procurement. However, there is still lack of knowledge and lack of experience. This research proposes a methodology applicable to any public entity for the inclusion of environmental criteria in its procurement processes, and was developed at Instituto Tecnológico de Costa Rica (ITCR) for purchase of office supplies. To this end, environmental criteria were determined with their respective evidences of verification and market consultations were carried out to determine the feasibility of compliance. Finally, the criteria were classified according to the current legislation. These findings reflect the lack of capacity to respond to environmental criteria, the importance of conducting market studies, and the need for training providers to obtain better yields on tenders.